Efficacy of the Enteroadsorbent Silicol®gel in Adults with Irritable Bowel Syndrome Subtypes IBS-D or Mixed: Observational Open-Label Study - Gordon Crawford; Rory Taylor; David Young; Chris G. Hatton (Gastroenterology Research and Practice)
Background. Irritable bowel syndrome (IBS) is a common chronic gut-brain interaction disorder with limited effective treatment options. Intestinal adsorbents have a high adsorption capacity for gut irritants and may provide nonpharmacological alternatives. Objectives. This post marketing study is aimed at providing up-to-date evidence to support the safety and efficacy in normal use of an established medical device for IBS treatment. Methods. In this open-label, observational study, adults with IBS with predominant diarrhoea (IBS-D) or IBS with mixed bowel habits (IBS-M), according to Rome IV criteria, received 4 weeks of treatment with the enteroadsorbent Silicol®gel, a CE-certified, licenced, medical device containing colloidal silicic acid. Eligible participants were assessed at baseline (visit 1; in-clinic) and after 1 (visit 2; telephone), 2 (visit 3; telephone), and 4 (visit 4; in-clinic) weeks of treatment. The primary endpoint was the proportion of participants with an overall reduction in the IBS severity scoring system IBS SSS>50, representing clinically meaningful improvement. Key secondary endpoints were a reduction in common IBS symptoms and improved quality of life (QoL). Results. Among the 67 treated participants (IBS-D: 37; IBS-M: 30), 65 completed the study. At visit 4, 83.6% (56/67) of participants achieved a reduction in IBS SSS>50. The mean (standard deviation [SD]) IBS SSS was 323.4 (55.7) at visit 1 and 160.3 (90.3) at visit 4 (overall change: -163.1 (101.7); 95% confidence interval [CI] 138.3, 187.9, p<0.001). Compared with visit 1, significant reductions in the severity of all key IBS symptoms and overall improvement in QoL were observed at visit 4 (p<0.001), with improvements observed from visits 1 and 2. Conclusions. In this open-label study of participants with IBS-D and IBS-M, Silicol®gel provided clinically significant improvement in IBS symptoms, demonstrating that enteroadsorbents may be clinically beneficial in this population.